THE APPLICATION OF DIRECT DENTAL IMPLANTATION TECHNIQUE WITH TOTAL DEFECTS ON THE LOWER JAW WITH THE USE OF THE SYNTHETIC OSTEOPLASTIC MATERIAL “KLIPDENT PL” AND THE MEMBRANE “KLIPDENT MK” - A.V. Liubchenko; N.S. Kravtsov (Український стоматологічний альманах, 2018)
The technique of conducting a direct dental implantation allows to combine several surgical steps into one, and as a result to shorten the duration of dental treatment, to reduce the psychological and emotional tension of patients and to accelerate the recovery. Implantation with total defects allows you to avoid using removable structures, which in due time affects the quality of life and the aesthetic need of the patient. Osteoplastic materials are used to restore the volume of bone tissue and to accelerate the osseointegration of the implant. We decided to give a clinical assessment of the implants’ stability and the degree of atrophy of the alveolar ridge surrounding the implant. The assessment was done in relation to three, six and nine months after the direct dental implantation with total defects on the lower jaw, using the synthetic osteoplastic material “Klipdent PL” and the membrane “Klipdent MK” (“VladMiVa”).